Warm Water Administration Before Nebulization Improves Airway Clearance In Asthma - I Made Sudarma Adiputra; Kadek Mahendra Novita Rahayu (Stikes Wira Medika Bali, 2017)
Nowadays, population of asthma symptoms increased according to the life style of modern people. Giving warm water was self action therapy non-pharmacologically its benefit is to open the airway for asthma’s patient. The purpose of this study was gain more knowledge about the effect by giving warm water before nebulizer action toward to the smoothness asthma’s patient airway. This study took place at RSUD Bangli on June-July 2017. Method: Quasi Experimental Design With Two Groups Research Using Pretest-Posttest Design. About twenty samples taken using Non-Probability With Consecutive Sampling. In this research using two hypothesis such as Wilcoxon Signed Rank Test and Mann-Whitney U-Test. Result And Analysis: The Wilcoxon Signed Rank Test hypothesis results got about 0,002 p value. Than Mann-Whitney U-Test got about 0,029 p value. Mean that there were difference effects by giving warm water before nebulizer action toward to the airway smoothness of asthma patient. Discussion: By giving warm water resulting two effects, hydrostatic and hydrodynamic therefore the airway become permanent.